Transient ischemic attacks – the role of arterial spin labelling - Dinesh, Sreehari; Gupta, Dulari; Murumkar, Vivek; Gorthi, Sankar Prasad (European Journal of Clinical and Experimental Medicine, 2025)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction and aim. Transient ischemic attacks are usually diagnosed by clinical criteria. Arterial spin labelling (ASL) is a noninvasive technique based on magnetic labeling of hydrogen ions in arterial blood with high sensitivity for the detection of oligemic areas in the corresponding cerebral hemisphere to the clinical phenotype. The aim is to demonstrate hypoperfusion using Arterial spin labelling techniques in TIA cases with the objective of intervening with appropriate methods to stop the stroke progression. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Description of the cases. The authors analyzed 90 cases of TIA in order to ultimately select four cases of clinical TIA with Arterial spin labelling to test the proof of concept. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Case 1. 47-year-old male with transient right-sided limb weakness and corresponding ASL hypoperfusion. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Case 2. 57-year-old male with recurrent transient ischemic symptoms and ASL showing hypoperfusion in the right parietal lobe. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Case 3. 73-year-old male with a high risk TIA and right parietal hypoperfusion on ASL that evolved into an infarct. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Case 4. 30-year-old female with a sensory TIA and hypoperfusion in the right cerebral hemisphere on ASL. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">The hypothesis is that Arterial spin labelling will be able to demonstrate a penumbra in brain tissue in TIA cases which suggests likely progression to stroke and help in appropriate intervention to stop progression in real time. The following sequences were used during the brain MRI: diffusion-weighted imaging, fluid attenuated inversion recovery, apparent diffusion coefficient, and ASL sequences after written informed consent. Philips Ingenia 3Tesla machine obtains a 3D pseudocontinuous ASL sequence with a color coded map is obtained by Philips Ingenia 3 Tesla machine with a magnet weight of 4600 kg, 90-degree flip angle, and total duration of 3 minutes and 19 seconds. The authors present a series of 4 cases in which patients had clinical TIA and had hypoperfusion on ASL sequence correspond ing to the clinical manifestation depicting the penumbra. ASL hypoperfusion was assessed visually and cerebral blood flow (CBF) data was averaged to develop a visual CBF map. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. Arterial spin labelling is a novel marker for hypoperfusion that indicates brain parenchyma under threat due to either stenosis in vessels of the cerebral circulation or embolic phenomenon.